Interinstitutional agreement for the academic year 2010/2011 Lifelong Learning Programme, higher education (Erasmus) between Università degli Studi di Trento and Universidade Lusíada de Lisboa - Universidade Lusíada de Lisboa (2016)
- Cooperate in the activities within the Lifelong Learning Programme / Erasmus. - Subject area: Architecture and town planning.